Analysis of lightweight composite sections with reinforced concrete infill with autoclaved aerated concrete (AAC) - Okasha, Mostafa Ali Taha Ali; Abdel Razek, Mohamed; El-Esnawi, Hassan; Alkhatib, Soliman (Frontiers in Built Environment, 2023)
The development of composite sections is of great importance in structural design, with the aim of reducing weight and deflection while limiting the effect on the composite section’s strength and durability. This paper examines the computational analysis of composite sections where reinforced concrete was replaced with autoclaved aerated concrete (AAC) in the compression zone. The first principles of concrete combined with Hook’s law were adopted to find a flexure, shear, equivalent modulus of elasticity, effective moment of inertia, and deflection. The results are discussed and investigated using the finite element models developed by ANSYS WORKBENCH software. We found that the proposed analytical model can effectively provide a solution for the composite cross-section. The comparison between the theoretical calculation of the first cracking loads and the finite element percentage ranges from 89 to 110%. The ratio of the computational calculation of the modulus of elasticity to the finite element results ranged from 0.91 to 1.06. The comparison between the theoretical calculation of the effective moment of inertia to the finite element percentage ranged from 92% to 118%. The ratio of the computational calculation deflection to the finite element ranged from 0.87 to 1.15.